Transition to the Non-Clinical Drug Development Principles and Rules of the Eurasian Economic Union: Changes, Challenges, and Prospects - A. A. Spasov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
It is strategically critical to secure pharmaceutical independence for Russia by developing the industry using the latest achievements in science and technology. The development of nationally and internationally competitive medicines calls for the harmonisation of national and international requirements for non-clinical and clinical studies.In this interview, Alexander A. Spasov, Academician of the Russian Academy of Sciences, Doctor of Medical Sciences, Full Professor, Head of the Department of Pharmacology and Bioinformatics of the Volgograd State Medical University, voices his authoritative opinion on the changes to the regulatory requirements for non-clinical and clinical studies of medicinal products that are related to the transition of the Russian Federation to the Eurasian Economic Union marketing authorisation requirements. Alexander A. Spasov touches upon the development and application potential of cutting-edge research methods (in silico, human cell-based and alternative animal-based methods) for the creation and implementation of more reliable and rapid test systems for pharmacology and toxicity studies.